2001
DOI: 10.1097/00006324-200106000-00020
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Six Months of Contact Lens Wear on the Tear Film, Ocular Surfaces, and Symptoms of Presbyopes

Abstract: These results provide a representation of the ocular surface condition and symptoms of ocular discomfort in the middle-aged population and seem similar to reports of younger populations. Wearing contact lenses seems to influence dry eye symptoms more than age or gender. Therefore, presbyopes should not be excluded from consideration for contact lens fitting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 25 publications
5
41
3
Order By: Relevance
“…[12][13][14][15][16] Other studies however did not find any sex difference in corneal sensitivity. 17,18 Future studies are needed to confirm and further explore these differences, but also to clarify the exact role of ocular surface sensitivity in the symptomatology of DED.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 82%
“…[12][13][14][15][16] Other studies however did not find any sex difference in corneal sensitivity. 17,18 Future studies are needed to confirm and further explore these differences, but also to clarify the exact role of ocular surface sensitivity in the symptomatology of DED.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 82%
“…Previous studies have already shown the lack of association between DED symptoms and ocular surface signs [51] and age [52]. Reduction of the tear secretion in dry eye patients induce inflammation and peripheral nerve damage [53].…”
Section: Discussionmentioning
confidence: 98%
“…It is of note that women apparently produce less foam in the canthus (76). In a study of presbyopes, women had more epithelial damage of the conjunctiva, more sensitive eyes (ie, lower corneal threshold), and lower break-up time than men after 6 months of wearing contact lenses (145). All in all, women appear to exhibit lower tear film stabilities than men (154).…”
Section: Eye Irritation In Relation To Gendermentioning
confidence: 97%
“…With a similar approach, but with building materials as sources of VOC, an association was found between reduced tear film quality (pooled break-up time, foam formation, and thickness of lipid layer) and an increase in reported eye irritation (136). In a field study, a weak association was observed between an increase in polymorphonuclear neutrophils in the eye and VDU work (76 ] Reports of dry eyes among a presbyope population increased from 28% before contact lenses were acquired to 68% after 6 months of use, and complaints were the most pronounced among women (145). The use of contact lenses appears to influence dry eye symptoms more than age and gender (145,146).…”
Section: Eye Irritation In Relation To Exposure To Indoor Air Pollutionmentioning
confidence: 99%
See 1 more Smart Citation